Structuring Strategy of Regional Technical Implementation Unit (UPTD) Regency: (Case Study: Organization and Governance Section of Penajam Paser Utara Regency) - Rini Wedhayanti (PT Mattawang Mediatama Solution, 2023)
This study was conducted to explain the Strategy of Organizational Structuring Policies that have been implemented in Penajam Paser Utara Regency. This study aims to describe the strategy through the basis of Osborne and Gaebler's (2014) theory. This study takes a descriptive qualitative research design. Data collected were through interviews, observations, and documentation. The findings show that arrangement of Local Technical Unit in PPU Regency only had use three strategies involving Core, Customer and Control Strategies by both of Organizational through the institutional review, and institutional product and police by community. Meanwhile, the required strategy involved Core, Customer and Control, Consequence, and Culture Strategies. The UPTD organizational arrangement in Penajam Paser Utara Regency is carried out only with core strategy, control strategy, and customers strategy. In addition, there are five strategies needed by the East Kalimantan Provincial Organization Bureau and the Organization and Administration Division of Penajam Paser Utara Regency Distruct.